Analysis of Business Feasibility Study in Bottled Drinking Water of PT. Amiro in Uma Jero Village, Busungbiu District, Buleleng Regency - WIYANTI, NI KETUT PURANI; BUDIASA, I WAYAN; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Analysis of Business Feasibility Study in Bottled Drinking Water of PT. Amiro in Uma Jero Village, Busungbiu District, Buleleng Regency. Water is a major component in the human body, without which creatures cannot grow and develop. Drinking water is a major component of the body; on average each person has 70-80 percent of water from his body weight. The community has now switched from consuming ordinary drinking water which is cooked into bottled water. Companies engaged in the BDW sector keep increasing and continue to expand their product networks. The purpose of this study was to determine the bottled drinking water business at PT. Amirowhether it is financially feasible in terms of investment criteria, namely NPV, IRR, Net B / C, Payback Period and Sensitivity Analysis and the goal of the study was also to identify the constraints faced by PT. Amiro in running a business. Based on this research, it could be seen that the NPV value wasRp. 12,640,670,205, IRR 35.79%, Net B / C 3.64, and the Payback Period was 8 years 3 months, therefore it means that BDW business of PT. Amirois financially feasible to be carried out. Constraints in the feasibility study of PT. Amiro, in developing the business process were that the licensing process took a lot of time to meet the requirements needed to obtain a business license such as the Agency of Food and Drug Control, Indonesian National Standard, Halal Certificate from MUI and ISO 9001. Amiro is a new player in the BDW business and is not yet known by the public so it needs a strategy to get market share from a very dense market.